Endocranial morphology of Pygoscelis calderensis (Aves, Spheniscidae) from the Neogene of Chile and remarks on brain morphology in modern Pygoscelis - Paulina Carabajal, Ariana; Acosta Hospitaleche, Carolina Ileana Alicia; Yuri Yáñez, Roberto (Historical Biology)
The endocranial anatomy of Pygoscelis calderensis, a fossil species from the Bahía Inglesa Formation (Middle Miocene–Pliocene) of Chile, South America, was described through CT scans. Reconstructions of the fossil P. calderensis and endocasts for the living Pygoscelis adeliae, and Pygoscelis papua are provided here for the first time. Comparisons with the extant congeneric species P. adeliae, Pygoscelisantarctica and P. papua indicate that the morphological pattern of the brain and inner ear of the extant pygoscelids has been present already in the Middle Miocene. The neurological morphology suggests that the paleobiology of the extinct form would have been similar to the extant species. It was probably true for diet, feeding behaviour and diving kinematics. Fil: Paulina Carabajal, Ariana. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Museo Carmen Funes; Argentina Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Museo de la Plata; Argentina Fil: Yuri Yáñez, Roberto. Universidad de Chile; Chile